The "Smart Work" Myth: How Bureaucratic Inertia and Workplace Culture Stymied Digital Transformation in the Relocation of South Korea's Capital. - Hur, Joon-Young; Cho, Wonhyuk; Lee, Geon; Bickerton, Sarah Hendrica (Asian Studies Review, 2019)
Starting in 2012, the South Korean government has implemented a large-scale relocation of its central government agencies, which are now split between the existing capital city (Seoul) and a new administrative-capital city (Sejong). One of the most controversial aspects of the relocation has been the bureaucratic inefficiency caused by its split nature. ICT-enabled solutions, dubbed "Smart Work", were adopted to deal with this challenge, but have not been effective in avoiding inefficiency. In this article, we argue that different forms of organisational inertia created resistance to switching from traditional work routines to Smart Work's ICT-assisted equivalents. Various forms of inertia – psychological (anxiety around learning new technologies), cognitive (culture/norms in face-to-face work routines), technological (stickiness of pre-existing IT system), political (continued influence from elected officials), and resource allocation (success bias from previous digital government projects) – significantly influenced public managers' work practices in Sejong. These types of inertia, we argue, have reinforced face-to-face communication rather than digital communication, on-site visits rather than video-conferencing, and fixed-time work rather than flex-work. Our findings challenge dominant views from functionalist models of digital transformation and emphasise the importance of cultural congruency between workplace norms and technophilic business processes.